Serum parameters and energy balance during the Yukon Arctic Ultra: a multistage ultramarathon in Arctic conditions - Schalt, Adriane K.; Coker, Robert H.; Gunga, Hanns-Christian; Kienast, Camilla; Mascarell-Maricic, Lea; Steinach, Mathias (Frontiers in Nutrition, 2026)
PurposeThe objective of this study is to focus on energy intake and expenditure, as well as changes in various serum parameters regarding stress and metabolism, during the Yukon Arctic Ultra (YAU), an ultramarathon of 690 km length, under Arctic conditions.MethodsThe Yukon Arctic Ultra was studied over 4 years (2013, 2015, 2017, and 2019). A total of 22 participants (14 men, 8 women) were recruited, who raced on foot while pulling a sled. At four different checkpoints (PRE 0 km; D1 277 km; D2 383 km, and POST 690 km), measurements were performed.ResultsA total of 14 participants finished (FIN) the race successfully (9 men; 5 women), 8 participants dropped out; total body weight loss in FIN men was 4.9 ± 2.1 kg, and in FIN women, 3.2 ± 1.8 kg. Total energy intake in FIN was 53,049 ± 10,474 kcal and 4,840 ± 819 kcal/day. Energy expenditure in FIN totalled 71,539 ± 10,585 kcal and 6,628 ± 1,019 kcal/day, resulting in a caloric deficit. Troponin T and CK showed significantly lower values in the slower participants at POST (diff means: 8.2 pg./mL and 417 U/L, respectively). CRP and NT-pro BNP increased at D1 (diff means: 16.5 mg/dL and 322.4 pg./mL, respectively), LDL decreased at POST (−45.5 mg/dL), as well as cholesterol, triglycerides, and non-HDL. Triiodothyronine (fT3) and thyroxine (fT4) decreased at POST (−1.0 and −1.8 pg./mL, respectively).ConclusionA considerable energy deficit was identified in almost all athletes, which resulted in the loss of both lean mass and fat mass. Serum cardiac, lipid, and inflammation markers were altered significantly, indicating severe stress. It remains to be seen whether such events contribute to pathological sequelae or are merely temporary without clinical relevance.